KEPEMIMPINAN KHARISMATIK VERSUS KEPEMIMPINAN VISIONER - Fauzan Fauzan (Al'Adalah, 2019)
The term of leadership is one of topic which is always interesting to be discussed and studied, because it is always observed and the phenomenon is less understanding. Leadership phenomenon in Indonesia has given a huge influence on politic and nation. The progress and the decrease of organization depends on leadership style, thus in institution such as educational institution and Islamic boarding school. If the educational institution has good leadership style, so it will get fast progress.